Synthesis of Polystyrene-Coated Superparamagnetic and Ferromagnetic Cobalt Nanoparticles - Tan, Li (Polymers (Basel), 2018)
Polystyrene-coated cobalt nanoparticles (NPs) were synthesized through a dual-stage thermolysis of cobalt carbonyl (Co(2)(CO)(8)). The amine end-functionalized polystyrene surfactants with varying molecular weight were prepared via atom-transfer radical polymerization technique. By changing the concentration of these polymeric surfactants, Co NPs with different size, size distribution, and magnetic properties were obtained. Transmission electron microscopy characterization showed that the size of Co NPs stabilized with lower molecular weight polystyrene surfactants (M(n) = 2300 g/mol) varied from 12–22 nm, while the size of Co NPs coated with polystyrene of middle (M(n) = 4500 g/mol) and higher molecular weight (M(n) = 10,500 g/mol) showed little change around 20 nm. Magnetic measurements revealed that the small cobalt particles were superparamagnetic, while larger particles were ferromagnetic and self-assembled into 1-D chain structures. Thermogravimetric analysis revealed that the grafting density of polystyrene with lower molecular weight is high. To the best of our knowledge, this is the first study to obtain both superparamagnetic and ferromagnetic Co NPs by changing the molecular weight and concentration of polystyrene through the dual-stage decomposition method.